Correlation of Wellness Program Against Degenerative Indicators Through Experimental Pre-Posttest - Suandy, Suandy; Susianto, Susianto; Handoko, Erwin; Luwis, Kevin; Sanoesi, Vindelin (Jurnal Kedokteran Brawijaya, 2024)
The incidence of degenerative diseases, such as hyperuricemia, hypercholesterolemia, obesity, hypertension, and diabetes mellitus, is increasing, primarily due to unhealthy lifestyles. Holistic treatment, involving pharmacology and lifestyle modification, is recommended. The Wellness program, covering diet, exercise, and relaxation techniques like meditation and yoga offers a holistic approach to reduce the incidence of degenerative diseases. Adopting a Wellness program could have positive outcomes, including cost-effectiveness, nutritional balance, and improvements in both physical (through yoga) and mental (through meditation) well-being, but the potential downsides include lack of control groups, inadequate consideration of age and gender, insufficient sample sizes, limited observation days, and an excessive number of measured parameters. This study aims to see the effectiveness and influence of the Wellness program on reducing uric acid levels, cholesterol, blood sugar levels, systolic and diastolic blodd pressure. The intervention is designed for women aged 30-60 who experience rage. However, individuals who are consuming medications or supplements, pregnant, breastfeeding, or not following a prescribed diet are excluded. This study used the quasi-experimental pre-posttest design to see the Wellness program’s effectiveness on uric acid, blood pressure, blood sugar levels, and total cholesterol. Sample size calculation was performed using G*Power version 3.1.9.7, and data analysis utilized the T-paired sampled test. The findings from a 3-day study involving 47 participants revealed significant differences post-implementation of the Wellness program, indicating a reduction in uric acid levels and an increase in blood sugar levels with a p-value<0.05.